PENYELESAIAN SENGKETA E-COMMERCEMELALUI ODR (ONLINE DISPUTE RESOLUTION) - Widaningsih, Widaningsih (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2017)
E-commerce is a trading system that utilizes information technology and is an innovative trading system that enables fast electronic transactions across the world. Utilization of e-commerce transactions can cause trade dispute due to the process of buying and selling transactions electronically. The balance of creditor and debtor positions is paramount in both conventional and electronic trade transactions. In online trading transactions, consumers are often confronted with irresponsible business actor behavior. This is made easier by business actors because the parties do not meet each other directly in the event of an agreement. Therefore, as in conventional trading, online or e-commerce transactions between business actors and consumers must also be given legal protection to consumers. There needs to be consumer protection efforts in the implementation of e-commerce transactions either before the dispute or after a dispute. The purpose of this research is to find out the settlement of business dispute based on law in Indonesia, to know the process of business dispute resolution through ODR, and to know the position of ODR in legal dispute business dispute settlement in Indonesia. The research used in this paper is normative legal research by reviewing and analyzing secondary data data in the form of legislation - the invitation, primary data data in the form of legal books and journals related law journals, as well as tertiary data in the form of websites - websites from the internet . Based on data analysis conducted, it is concluded that ODR is an appropriate model of settlement to resolve international trade disputes. The rule of law on ODR is necessary so that the position of ODR in Indonesian law becomes clear and gives certainty to the community about the use of ODR in Indonesia.ODR online dispute resolution) is an alternative solution by utilizing information technology tools to interact online.